On-chip CMOS wireless sensors interface for automotive applications - Carmo, João Paulo Pereira (2004)
This paper describes a CMOS interface for short-range wireless sensor networks. The sensor interface is composed by the sensor readout and a transceiver in CMOS 0.18 µm process technology and a patch antenna at 5.7 GHz frequency, 50 MHz bandwidth and an efficiency of 18%. Automotive applications are the target of this wireless sensor interface.